2011
DOI: 10.1099/jmm.0.033092-0
|View full text |Cite
|
Sign up to set email alerts
|

Rhodomyrtus tomentosa (Aiton) Hassk. ethanol extract and rhodomyrtone: a potential strategy for the treatment of biofilm-forming staphylococci

Abstract: The anti-staphylococcal activity of an ethanol extract of Rhodomyrtus tomentosa and its pure compound, rhodomyrtone, as well as their effects on staphylococcal biofilm formation and biofilm-grown cells were assessed. MIC and minimal bactericidal concentration values of the ethanol extract and rhodomyrtone against planktonic cultures and biofilms of five clinical strains each of Staphylococcus aureus and Staphylococcus epidermidis, and American Type Culture Collection (ATCC) strains of both species, were 32-512… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
51
1
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 72 publications
(54 citation statements)
references
References 22 publications
0
51
1
2
Order By: Relevance
“…Providone iodine also inhibits biofilm formation and decreases transcription of the ica operon (38). The effects of natural antibacterial agents, such as berberine, carvacrol, farnesol, oregano, rhodomyrtone, and thymol, against staphylococcal biofilms have been frequently reported (24,37,47,54). Oregano, carvacrol, and thymol exhibit antistaphylococcal activity in biofilms.…”
Section: Discussionmentioning
confidence: 99%
“…Providone iodine also inhibits biofilm formation and decreases transcription of the ica operon (38). The effects of natural antibacterial agents, such as berberine, carvacrol, farnesol, oregano, rhodomyrtone, and thymol, against staphylococcal biofilms have been frequently reported (24,37,47,54). Oregano, carvacrol, and thymol exhibit antistaphylococcal activity in biofilms.…”
Section: Discussionmentioning
confidence: 99%
“…Saising et al [37] suggested that rhodomyrtone had significant effects on both biofilm formation and the survival of the organisms in the established biofilms. Hence, rhodomyrtone is reported to have the potential for further drug development for the treatment of biofilm-forming staphylococcal infections.…”
Section: Antibacterial Activitymentioning
confidence: 99%
“…[22] Taraxerol (32) [29] Trans-triacontyl-4-hydroxycinnamate (33) [26] 3,3',4,4'-tetra-O-methylflavellagic acid (34) [26] 3-O-(E)-coumaroyloleanolic acid (35) [26] (-)-(2R,3R)-1,4-O-diferuloylsecoisolariciresinol (36) [26] Arjunolic acid (37) [26] 4-hydroxy-3-methoxybenzoic acid (38) [26] Stigmast-4-en-3-one (39) [26] Oleanolic acid (40) [26] Methyl gallate (41) [26] 3-O-methylellagic acid 4-O-rhamnopyranoside (42) [26] …”
Section: Antifungal Activitymentioning
confidence: 99%
“…The compound was isolated from Rhodomyrtus tomentosa (Aiton) Hassk. leaves and exhibits pronounced antibacterial activity against a wide range of Gram-positive bacteria (Limsuwan & Voravuthikunchai, 2008;Saising et al, 2008;Limsuwan et al, 2009a;Voravuthikunchai et al, 2010;Saising et al, 2011). The MIC and minimum bactericidal concentration values of rhodomyrtone against MRSA range from 0.39 to 0.78 mg ml 21 , which is very close to those of vancomycin (Limsuwan et al, 2009b).…”
Section: Introductionmentioning
confidence: 64%